Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.18632/oncotarget.26867
|View full text |Cite
|
Sign up to set email alerts
|

Target HER four in breast cancer?

Abstract: The HER4 receptor tyrosine kinase is known to have promiscuous activity in malignant cells, last but not least in breast cancer. Evidently, the prognostic and predictive impact of HER4 expression depends on the expression of different receptor isotypes, the way of receptor activation (ligand dependent vs. independent), and on the complex interaction of the HER4 intracellular domain (4ICD) with intracellular regulative molecules which results in either oncogenic or rather tumor suppressive HER4 activity. Recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
(35 reference statements)
0
6
1
Order By: Relevance
“…In vitro studies in this cell line reported therapy resistance development to trastuzumab upon EGFR overexpression [17]. HER4 is a further candidate for forming heterodimers with other members of the HER family but the role HER4 plays in the course of breast cancer has long been unclear [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies in this cell line reported therapy resistance development to trastuzumab upon EGFR overexpression [17]. HER4 is a further candidate for forming heterodimers with other members of the HER family but the role HER4 plays in the course of breast cancer has long been unclear [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, ERBB4 functions to counteract the oncogenic activities of ERBB2 . It has been linked to the resistance to tamoxifen treatment and is associated with the stimulation of cancer cell proliferation [ 31 ]. Mutations in these two genes might be precursors of malignant transformation considering that they are frequently mutated in the case of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that ER/HER4 double positive ZR-75-1 BC cells were basically sensitive to TAM treatment, however, the treatment efficiency, represented by a reduced cell cycle progress and an increased fraction of quiescent (i.e., not cycling) cells could be considerably enhanced by a HER4 receptor knock-down [83]. Based on additional functional studies, by which 4ICD has been identified to operate as ER-coactivator [82,84,85], we assumed that a nuclear 4ICD and ER complex / interaction impairs the inhibitory effect of TAM, while the HER4 knock-down disables this interaction and thus raises the treatment efficiency [86]. We complemented the experimental evidence by quantitative analysis of HER4 expression in 258 BC specimens and identified a poor course and outcome of premenopausal and TAM treated BC patients with HER4-positive tumor tissues, whereas TAMtreated patients with low or absent tumor-associated HER4 expression performed significantly better.…”
Section: Intracellular Activities Of Her4 In Luminal Bc -The Subcellu...mentioning
confidence: 99%